Just mercy : adapted for young adults : a true story of the fight for justice - Stevenson, Bryan (Ember, 2019)
Lawyer Bryan Stevenson shares his efforts to end racial and economic injustice through his organization Equal Justice Initiative. With personal stories from his work, he sheds light on a broken justice system he's working to change.